Genetic and phenotypic parameter estimates for body weight and egg production at sexual maturity in Hilly×Fayoumi crossbred chickens - Das, Ashutosh; Gupta, Mukta Das; Khan, Md Kabirul Islam; Momin, Md Moksedul; Miazi, Omar Faruk (Asian Journal of Medical and Biological Research, 2018)
A crossbreeding experiment between Hilly, a locally adapted chicken type in Bangladesh and Fayoumi, an egg type light chicken breed was carried out to evaluate phenotypic performances and to estimate genetic parameters for body weight and egg production at sexual maturity. Results show the mean hatch weight of Hilly♂ × Fayoumi♀ (H♂×F♀) crosses was 35±0.1 gm. In this study, H♂×F♀ crossbred showed a heavier body weight (1551± 32.0 gm/bird) at 20 weeks in comparison with other indigenous chicken genotypes in Bangladesh. The highest body weight gain was found in 8-10 weeks of age. H♂×F♀ crossbred hens exhibited sexual maturity at an average age of 147.5±1.6 days with an average body weight of 1350± 16.8 gm/bird. The mean weight of eggs at sexual maturity was 33.7±0.5 gm/egg. The estimates of heritability for body weight were ranged from 0.15 to 0.26. We observed a positive genetic correlation between weight at sexual maturity (WSM) and egg weight at sexual maturity (EWSM), meaning that hens with high weight at sexual maturity would produce heavier eggs. Asian J. Med. Biol. Res. June 2018, 4(2): 186-192